EFEKTIVITAS PROGRAM RESITASI BERBASIS KOMPUTER UNTUK MENINGKATKAN PENGUASAAN KONSEP MAHASISWA TENTANG GAYA DAN GERAK - Sutopo, Sutopo (Pendidikan Fisika FKIP Unsri, 2016)
We have developed a computer-assisted recitation program to improve studentsâ conceptual understanding about force and motion. The program consists of multiple-choices questions with immediate feedback. The focus of this research was to examine the effectiveness of the program to achieve the goal, using one group pretest-posttest design. Pretest and posttest used the same instrument. Pretest was administered one week after the class discussed kinematics and Newtonâs laws of motion, whereas the posttest was administered three weeks later when the students had utilized the program for one week. Subject consisted of 35 first year physics education students enrolled in introductory physics, in State University of Malang. The research found that the program significantly improved studentsâ conceptual understanding with N-gain of 0.31 and d-effect size of 1.46.